Lipoprotein-inspired penetrating nanoparticles for deep tumor-targeted shuttling of indocyanine green and enhanced photo-theranostics. (3rd July 2019) - Sheng, Yu; Wang, Zhen; Ngandeu Neubi, Gella Maelys; Cheng, Hao; Zhang, Chenshuang; Zhang, Huaqing; Wang, Ruoning; Zhou, Jianping; Ding, Yang
Abstract : Biomimetic iRGD-rHDL/ICG nanoparticles exhibited deep tumor targeted shuttling of indocyanine green and enhanced phototherapy. Abstract : Since conventional chemotherapy has a variety of deficiencies and severe side effects, phototherapy has recently aroused great interest worldwide owing to its great potential towards theranostic applications. However, the physiological barrier of tumors hindered the penetration of therapeutic and imaging agents into the center of tumors. In this study, a novel biomimetic nanoplatform inspired by high-density lipoproteins (HDLs) was designed with deep tumor penetrating ability and integrated the clinical imaging agent indocyanine green (ICG) for synergistic phototherapy. Specifically, the HDL-protein was conjugated with the tumor-homing iRGD peptide via an applicable cross-linker to obtain a similar α helix structure, which served as an organizing scaffold for maintaining lipid nanoparticle structure. Our study illustrated that the mimicking nanoparticles shared nanosized diameters and superior biostability compared with free ICG. Once irradiated by NIR light, the encapsulated ICG could produce heat in localized ranges for photothermal therapy (PTT) and sufficient reactive oxygen species (ROS) for photodynamic therapy (PDT). Moreover, the fluorescence of ICG excited by NIR light effectively assisted in diagnosis. After intravenous injection, HDL mimicking nanoparticles could penetrate into deep tumors to realize enhanced phototherapy (PTT and PDT) under NIR laser irradiation. This biomimetic drug delivery system could open an avenue for the production of tailored theranostic nanoplatforms for personalized medicine in the near future.